2007
DOI: 10.1097/ede.0b013e3180646338
|View full text |Cite
|
Sign up to set email alerts
|

Carbonated Beverages and Chronic Kidney Disease

Abstract: These preliminary results suggest that cola consumption may increase the risk of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
80
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 26 publications
7
80
1
5
Order By: Relevance
“…The authors concluded that drinking cola beverages over time likely led to higher levels of phosphoric acid that caused kidney damage via mechanism of nephrocalcinosis. 28 This study was not able to explore the association between sugarsweetened beverages and CKD, as significant associations were seen with both sugar-sweetened colas and artificially sweetened colas, and further comparisons between sweetened versus nonsweetened noncola drinks were not made.…”
Section: Sugar-sweetened Beverages and Kidney Outcomesmentioning
confidence: 97%
See 4 more Smart Citations
“…The authors concluded that drinking cola beverages over time likely led to higher levels of phosphoric acid that caused kidney damage via mechanism of nephrocalcinosis. 28 This study was not able to explore the association between sugarsweetened beverages and CKD, as significant associations were seen with both sugar-sweetened colas and artificially sweetened colas, and further comparisons between sweetened versus nonsweetened noncola drinks were not made.…”
Section: Sugar-sweetened Beverages and Kidney Outcomesmentioning
confidence: 97%
“…As with the first prospective study, the exposure of more than one beverage daily in this study is less than the exposure studied in earlier studies that yielded significant results. 28,29 This study also did not provide information on antihypertensive medications that might have been important confounders and that might also have affected serum uric acid level. Bomback and colleagues and other reviewers caution readers to not interpret the "negative" study as dismissing the effects of sugar-sweetened beverages on hyperuricemia and CKD.…”
Section: Us Endocrinologymentioning
confidence: 98%
See 3 more Smart Citations